Cardiac rehabilitation nursing of a patient with chronic heart failure (1例慢性心力衰竭患者的心脏康复护理体会) - JIA Haizhen (贾海珍); TAN Juan (谭娟) (中西医结合护理)
This article summarized the nursing experience of a heart failure patient during cardiac rehabilitation process Key issues of nursing included the nursing evaluation and data evaluation in the early stage of cardiac rehabilitation; According to the relevant evaluation, the doctor formulated the exercise intervention plan; Nursing staff analyzed the nursing problems, formulated the nursing goal, and determined the nursing measures, including five prescriptions of cardiac rehabilitation, nursing techniques of Traditional Chinese Medicine, and evaluation of curative effect of cardiac rehabilitation. Cardiac rehabilitation is the application of a variety of cooperative and purposeful interventions to improve the quality of life of patients and prevent cardiovascular events. (本文总结1例慢性心力衰竭患者心脏康复的护理体会, 包括心脏康复前期的护理评估、资料评估; 根据相关评估, 医生制定运动干预方案; 护理人员分析护理问题, 制定护理目标, 确定护理措施, 包括心脏康复“五大处方”、中医护理技术; 最后对心脏康复进行整体的疗效评估。心脏康复是应用多种协同的、有目的的各种干预措施, 使患者改善生活质量, 回归正常社会生活, 并预防心血管事件的发生。)